FACTORS AND EFFECTIVE METHODS OF DEVELOPING COMMUNICATION SKILLS OF MENTALLY RETARDED STUDENTS - Abdunazarov Abdumutal Olimovich (Modern American Journals, 2025)
The article discusses the education of mentally retarded children and their adaptation to society and social life, as well as the wide range of opportunities and conditions created for the education of mentally retarded children. The peculiarities of the adaptation of mentally retarded children to social life, their preparation for independent activity are described, and the views on the essence of this issue are listed. The main goals and objectives of special boarding schools, as well as the need for constant cooperation between the subjects in the formation of independent thinking skills of the mentally retarded child.
Keywords: mentally retarded, children with special needs, social, special education, clinical pedagogical, oligophrenia, endogenous, exogenous, genetic factors, mental retardation, dementia, imbecility, idiocy.